(untitled) (International Journal of Management and Sustainability, 2023)
The development of batik in Indonesia is very rapid, and this can be seen from the growing number of batik producers. The management of batik MSMEs is still facing various interrelated problems, causing a decline in their performance. Through the resource-based theory (RBT) approach, this study aims to determine how internal resources at Batik UMKM in East Java can improve the performance of SMEs. The purpose of this study is to obtain empirical evidence of the influence of intellectual capital and entrepreneurial orientation on the performance of SMEs and to examine the innovation capability in mediating the influence of intellectual capital entrepreneurial orientation on the performance of batik SMEs in East Java. The population in this study comprises 140 owners of batik SMEs in East Java. Analysis of the data is done through structural equation modeling. The results showed that intellectual capital and entrepreneurial orientation had an influence on the performance of batik SMEs sampled. In addition, innovation capability was able to mediate the influence of intellectual capital and entrepreneurial orientation on the performance of the SMEs. The results of this study can enrich the repertoire of knowledge related to the resource-based theory and can improve the performance of batik MSMEs in East Java through the implementation of business strategies and the use of resources that include intellectual capital, entrepreneurial orientation and innovation capability.